Reevaluating Plastic Surgery in Modern Medicine: A Maqashid al-Shari’ah Approach to Aesthetic and Reconstructive Procedures - Nur Izatun Fauzi; Rifqi Rifqi (Lentera Peradaban: Journal on Islamic Studies, 2025)
The rapid advancement of medical science and technology has transformed the health sector, prioritizing patient satisfaction and aesthetic perfection. However, this progress often challenges established moral norms and the ontological nature of the human form, particularly in the realm of plastic surgery—or Jirahah Tajmil. Plastic surgery encompasses procedures aimed at enhancing or repairing body parts to improve function or aesthetics. From an Islamic legal perspective, a crucial distinction must be made between reconstructive surgery (hajah), which restores function and corrects congenital or accidental defects, and purely elective cosmetic surgery (tahsiniyyah) aimed at altering God's creation for vanity. This paper analyzes the boundaries of permissible medical intervention, arguing that while Islam encourages health and well-being, technological application must remain subservient to the preservation of human dignity and divine law.